The dependence of health insurance availability on years left before Medicare - Esra Eren Bayindir; Mehmet Yigit Gurdal; Ismail Sağlam (Koç University-TÜSİAD Economic Research Forum (ERF), 2011)
We study the dependence of health insurance availability of near-elderly inpatients in the United States with respect to their ages. We show that the likelihood that near-elderly inpatients are uninsured continuously declines until the early ages of 60 but the trend is reversed for the last few years preceding Medicare coverage. In addition, compared to those covered by Medicaid or private insurance, the uninsured patients are more likely to be admitted into hospitals as emergency cases.
Keywords: I11; 330; health insurance; Medicare; Krankenversicherung; Versicherungsschutz; Gesundheitsversorgung; USA